Fluorescence studies of potential antitumoral 6-heteroarylthieno[3,2-b]pyridines in solution and in nanoliposomes - Carvalho, M. Solange D. (2012)
Fluorescence properties of new potential antitumoral 6-heteroarylthieno[3,2-b]pyridines, recently synthesized, were studied in solution and in nanoliposomes of different compositions. The results indicate that these compounds can be transported in the hydrophobic region of the lipid bilayer. The liposomal formulation Egg-PC:Ch:DPPG (7:3:1) is the one with smaller size and lowest polydispersity.